Potentiometric Determination of the Dissociation Constant of Benzoic Acid in Aqueous Ethanol Solvents and Investigation of Effect of Solvent and Inorganic Salts on Spectroscopic Properties of Benzoic Acid Solutions by UV Absorbance Spectroscopy - Takin, Nalan (Asian Journal of Chemistry, 2016)
The dissociation constants of benzoic acid has been determined at 25°C and an ionic strength of 5 mmol L–1 in water and mixed aqueous solutions of ethanol (0.5–5%) by potentiometric measurements. A linear relationship between pKa and the mole fraction of the co-solvent was observed. In this study, the effect of concentration of ethanol in the solvent mixture and the adding inorganic salts to benzoic acid solutions on the absorbance of the solutions was examined. The measurements were performed by using a UV spectrophotometer. It has been shown that the solvents affect the dissociation equilibria and UV absorbance spectra of benzoic acid. This effect was related to the hydrogen bonding ability of the OH groups of the former class of anions.